Academic Senate Minutes 2004-05-20 - Academic Senate:::::::::
Chair's report. Agenda approved. Minutes of 4/22/04 approved. Interim Withdrawal policy approved. Candidates for Graduation approved. Academic Affairs Strategic Planning document – suggestion for change approved. Item moved to business for next fall. APC Statement regarding "A New Path for General Education at Sonoma State" including charge to EPC and GE subcommittee with developing a GE reform proposal to bring back to the Senate approved. Report on the Budget – President, Provost, Vice President of Administration & Finance. Dean Saeid Rahimi – B.S. in Engineering Science report. Statement from Campus Climate Committee on same-sex marriage endorsed. Installation of New Officers.